Welcome to demon school! : Iruma-kun. Vol. 2 - Nishi, Osamu (Kodansha USA Publishing, LLC, 2023)
"Despite his best efforts to avoid attention, Iruma's dumb luck and good nature have made him the talk of Babyls. But his unwanted fame has also caught the eye of the student council president, Ameri, who suspects that Iruma may not be the demon others think he is. As Iruma's string of uncanny feats continues, Ameri draws closer to the truth, and before long, their worlds come crashing together in a fateful and heart-pounding encounter"--